1997
DOI: 10.1073/pnas.94.21.11514
|View full text |Cite
|
Sign up to set email alerts
|

MIC-1, a novel macrophage inhibitory cytokine, is a divergent member of the TGF-β superfamily

Abstract: Macrophages play a key role in both normal and pathological processes involving immune and inf lammatory responses, to a large extent through their capacity to secrete a wide range of biologically active molecules. To identify some of these as yet not characterized molecules, we have used a subtraction cloning approach designed to identify genes expressed in association with macrophage activation. One of these genes, designated macrophage inhibitory cytokine 1 (MIC-1), encodes a protein that bears the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
915
4
15

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,031 publications
(951 citation statements)
references
References 39 publications
17
915
4
15
Order By: Relevance
“…The pro-form of this protein is a homodimer of a 308 amino acid polypeptide, whereas the mature form is a dimer of the last 112 amino acids. 9 The mature form of MIC1 contains no potential N-glycosylation sites but has been shown to be expressed and secreted in CHO cells by fusion with a secretion signal peptide. 9 When an NXS/T sequon was introduced at the N-terminal of the protein (D201S, 198RNGSH, two amino acid behind an N-terminal six histidine tag), the secretion of the mature MIC1 mutant dimer increased more than about five-fold in HEK293-6E cells.…”
Section: Introduction Of N-glycosylation Site On Proteins Lacking Effmentioning
confidence: 99%
“…The pro-form of this protein is a homodimer of a 308 amino acid polypeptide, whereas the mature form is a dimer of the last 112 amino acids. 9 The mature form of MIC1 contains no potential N-glycosylation sites but has been shown to be expressed and secreted in CHO cells by fusion with a secretion signal peptide. 9 When an NXS/T sequon was introduced at the N-terminal of the protein (D201S, 198RNGSH, two amino acid behind an N-terminal six histidine tag), the secretion of the mature MIC1 mutant dimer increased more than about five-fold in HEK293-6E cells.…”
Section: Introduction Of N-glycosylation Site On Proteins Lacking Effmentioning
confidence: 99%
“…The protein encoded by NAG-1, which has been isolated by a variety of cloning strategies, is also known as macrophage inhibitory cytokine-1 (MIC-1) (Bootcov et al, 1997), placental transforming growth factor β (PTGFB) (Tan et al, 2000), prostate derived factor (PDF) (Paralkar et al, 1998), growth differentiation factor 15 (GDF15) (Hsiao et al, 2000) and placental bone morphogenetic protein (PLAB) (Hromas et al, 1997). The diversity of biological functions indicated by this nomenclature suggests that the biological role of the NAG-1 protein depends on cell context.…”
Section: Introductionmentioning
confidence: 99%
“…GDF-15, or macrophage inhibitory cytokine 1, was originally identified as a factor secreted by activated macrophages (5). Sequence analysis has shown that it is a more distant member of the TGF␤ family (6); GDF-15 shares its homology based on the typical TGF␤ cysteine domains, but shares Ͻ30% sequence homology with other family members such as TGF␤1, GDF-5, and bone morphogenetic proteins.…”
mentioning
confidence: 99%